Unlearning organized numbness through poetic synesthesia: A study in scarlet. Issue 4 (September 2022) - Pérezts, Mar
I define "organized numbness" as the organized inability to perceive sensations, a learned desensitization operating in the way our (1) bodies, (2) language, and (3) knowledge are organized. I propose poetic synesthesia's power to associate several sensory perceptions as a way to unlearn this sort of disembodied habituation. Inspired by the so-called "accursed" French poets of the 19th century, the "long, prodigious, and rational disorganization of all the senses" of synesthesia helps me propose a method for unlearning organized numbness. I illustrate this by "a study in scarlet, " that is, by plunging into the depths of a synesthetic exploration of blood as my "fil rouge" to infuse our working bodies with renewed sensorial and embodied—or rather "embloodied"—life. I end by discussing how cultivating poetic synesthesia can help us unlearn organized numbness in the body, in language, and in knowledge, and how it can instead respectively foster resonance by learning (1) a different embodied habituation of sensorial sensitivity, (2) a language that instead of abstracting us from the senses actually allows us to reconnect with them and to delve deeply into their combined and thereby potentiated power, and (3) an epistemological gateway to the "unknown."